Realizing Welfare State and Social Justice: A Perspective on Islamic Law - Agus Riwanto; Sukarni Suryaningsih (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
The function of the state in exercising power is to ensure social justice for its people. To make it happen, efforts are needed to explore the concept of statehood. In its development there are two concepts of statehood, namely the welfare state and liberal states or capitalism state. Both are different and tend to be contradictory. This article aims to study and explore about Maqashid As-shari'ah (the principles or purposes of Islamic law) in order to bridge the conflict between the two concepts of statehood. The method used is socio-legal research, which is legal research using interdisciplinary. Data is obtained from the library or library recearch. The results showed that the concept of the welfare state demands the role of the state in distributing socio-economic justice, while the concept of a liberal state marginalizes the role of the state in the distribution of socio-economic justice and submits to market mechanisms. In state practice the concept of a liberal state defeats the concept of a welfare state. As a result the function of the state shifted towards the market and turned its face into an inhuman capitalist economy. Islam can be used as a solution and bridge the conflict between the two concepts of statehood. By placing the politics of Islamic law based on the Maqasid asy-Shari'ah as the solution, namely putting the principles of shari'ah economy in the form of banning usury, prioritizing justice, togetherness and prudence which in practice can be a Shari'ah business, as reflected in Law Number 21 of 2008 concerning the Development of Shari'ah and the principle of good governance according to Shari'ah in the form of shiddiq (honest), istiqamah (firm in the establishment), fathanah (intelligence: ratio, taste and divinity), trust (accountability).